ANALISIS ISI PESAN AKHLAK DALAM NOVEL KEKASIH IMPIAN KARYA WARDAH MAULINA - Imam Sobirin; Elang Bahrudien (Melati Institute, 2022)
Wardah Maulina's novel entitled Kekasih Impian tells the romantic journey to marriage life. It is a journey from short friendship on social media to love.. Natta immediately proposes Wardah Maulina without dating. He believes in his faith to do ta’aruf. This research is a qualitative descriptive study. The subject of this studyis the novel Kekasih Impian by Wardah Maulina. This study focuses on the analysis of moral messages with a pragmatic approach. Data were analyzed with qualitative description techniques.It is a research procedure which the results of descriptive data presentated in the form of the novel author's speech. The method of data collection is conducted by reading and note taking techniques.The results showed that the moral message contained in the novel Kekasih Impian consists of the messages of God and human being morality. The message of the Almighty God morality will form the religious education. The principal morals of God cover faith, ihsan, piety, resignation, gratitude, sincerity andpatience. Islamic humans morality or akhlak includes akhlak to the Messenger of Allah, parents, oneself, families, neighbors, and society. The Islamic ethic or akhlak on the environment includes being conscious to maintain the preservation of the environment, to protect and utilize the nature, especially animals andplants, and human being. The fictional elements used as a moral messenger are themes, settings, characters and language styles. The theme used in the novel Kekasih Impian includes the main and additional themes.